Digital Marketing Strategy Analysis “Lagoon Avenue Mall” Toward Sustainable Development Goal 5 (Case Study at Lagoon Avenue Mall Sungkono Surabaya) - Ayu Sekar Ndini; Prima Mulyasari Agustini (Humanities, Society, and Community, 2024)
This study examines the digital marketing strategy of Lagoon Avenue Mall Sungkono Surabaya, Indonesia, in promoting Sustainable Development Goal 5 (SDG 5), focusing on women’s empowerment. Employing a qualitative approach, the study delves into the strategies implemented by the mall’s internal team and provides insights from community partners and event organizers who have collaborated with the mall. The combination of internal and external perspectives provides a comprehensive view of digital marketing efforts and challenges faced in achieving SDG 5. Findings indicate that while Lagoon Avenue Mall has succeeded in targeting specific market segments and developing mall-based events, several areas require enhancement. Challenges include imprecise audience targeting, inadequate campaign performance evaluation, lackluster content, and low user engagement. Administrative issues related to rental contracts, uncertainty about non-financial collaboration benefits, and competition from other malls also pose significant obstacles. This study offers actionable recommendations for improving digital marketing strategies to support SDG 5 goals, particularly empowering women. By refining these strategies and addressing the identified challenges, Lagoon Avenue Mall can more effectively contribute to sustainable development and meet the objectives of the SDG agenda.